The Related Factors To Decreased The New Graduate Nurses Work Stress Level Of In Semarang - ARIEF YANTO; SRI REJEKI (Fakultas Ilmu Keperawatan Universitas Islam Sultan Agung, Semarang, 2017)
Background: The new graduate nurses have been in a stressful situation about their workplace. The High level of work stress has been decreased the nurse’s motivation in the work, so it will have an impact on the decline the nursing services quality. The new graduate nurses with the work stress will be motivated to quit their jobs. Objective: This study aims to determine the factors associated with decreased job stress of new graduate nurses. Method: This study was a quantitative research. The data was analized with the associative analytic method and cross sectional approach. The population of this study was all new graduate nurses who have had experience for 1-6 months. The sample size is determined by total sampling technique of 30 nurses. The study was conducted at Semarang Medical Center. Work stress measurement using DASS 42 instrument. The analysis process of the data performed using Spearman rank test and multiple linear regression to measure the relation of factors related to work stress. Result: The new graduate nurses work stress has a normal until light category. The average value of new graduate nurses work stress was 27, with the minimum and maximum score 8-40. The factors that have been eligible for the multivariate analysis of new graduate nurses work stress reduction were age and the mentoring programs. The result of the multivariate test showed that nurse ages together with the mentoring program had significant effect to the decreased of new graduate nurses work stress (p-value = 0,007). Discussion: Has increased of ages have been improved adaptability and positive response to stressors. The mentoring was the process of coaching for the new graduate nurses. Mentoring can be used as a support system for new graduate nurses in facing the transition from student to being nurses. The combination of increased the ages and the mentoring programs have been reduced the new graduate nurses work stress.